Calidad del agua y la desnutrición en menores de 5 años en la región Amazónica del Ecuador - Agila Yaguana, Lucy del Cisne (2025)
Water pollution directly affects health, perpetuating cycles of disease and malnutrition, especially in rural and indigenous communities. The objectives were: To identify water quality and the prevalence of malnutrition in children under 5 years of age in the Amazon region and to design an educational strategy to visualize the results. A cross-sectional ecological observational study was conducted based on data from the ENDI 2022-2023 survey to characterize sociodemographic variables, malnutrition, and water quality in children under 5. It was identified that 52.4% of the population under 5 years of age in the Amazon region are girls, and 59.7% reside in rural areas. 30.9% belong to the lowest income quintile, concentrated in the provinces of Napo and Sucumbíos. Ethnically, the majority are mestizos 62.9%, followed by indigenous 34.4%, with higher concentrations of indigenous population in Napo 10.39% and Morona Santiago 6.64%. Chronic malnutrition in children under 5 years of age affects 79.1%, with higher prevalence in Pastaza 16.9% and Zamora Chinchipe 14%. In addition, 88.3% of the water from the source and the point of consumption lacks chlorine, while 22.2% has high levels of contamination by E. coli. Using the Power BI graphical interface, these results were published interactively on the UNL website. It is necessary to strengthen public policies and community education to improve water quality and reduce malnutrition, emphasizing accessible information strategies